Cerebral response to emotional working memory based on vocal cues: an fNIRS study - Ohshima, Saori; Koeda, Michihiko; Kawai, Wakana; Saito, Hikaru; Niioka, Kiyomitsu; Okuno, Koki; Naganawa, Sho; Hama, Tomoko; Kyutoku, Yasushi; Dan, Ippeita (Frontiers in Human Neuroscience, 2023)
Introduction Humans mainly utilize visual and auditory information as a cue to infer others’ emotions. Previous neuroimaging studies have shown the neural basis of memory processing based on facial expression, but few studies have examined it based on vocal cues. Thus, we aimed to investigate brain regions associated with emotional judgment based on vocal cues using an N-back task paradigm. Methods Thirty participants performed N-back tasks requiring them to judge emotion or gender from voices that contained both emotion and gender information. During these tasks, cerebral hemodynamic response was measured using functional near-infrared spectroscopy (fNIRS). Results The results revealed that during the Emotion 2-back task there was significant activation in the frontal area, including the right precentral and inferior frontal gyri, possibly reflecting the function of an attentional network with auditory top-down processing. In addition, there was significant activation in the ventrolateral prefrontal cortex, which is known to be a major part of the working memory center. Discussion These results suggest that, compared to judging the gender of voice stimuli, when judging emotional information, attention is directed more deeply and demands for higher-order cognition, including working memory, are greater. We have revealed for the first time the specific neural basis for emotional judgments based on vocal cues compared to that for gender judgments based on vocal cues.